Genome Sequencing Reveals the Adaptation of Chickens to High Altitudes in Different Regions - Yizhou Hu; Xing Li; Qixin Guo; Lan Huang; Hao Bai; Guobin Chang (Animals, 2025)
Altitudinal adaptation is a key factor in species formation and leads to increased species diversity. Chickens are one of the most widely distributed and important domesticated species, making them ideal models for studying the evolution of altitudinal adaptation. Therefore, we downloaded and analyzed the total genome data of 160 individual chickens from seven sampling regions at two different altitudes (>3000 m and <600 m). In total, 21,672,487 high-quality single-nucleotide polymorphisms were selected and used for subsequent analyses. First, we interpreted the genetic relationships among chickens from different sampling regions using a neighbor-joining tree, population structure, and four dimensionality reduction methods. We found that 38 genes were significantly associated with altitudinal adaptations by FST and θπ. Functional annotation of the genes showed that they are primarily involved in energy metabolism, ion channel activity, and blood pressure regulation. Our results provide evidence of genetic diversity among different chicken breeds and reveal the mechanisms of adaptation to high altitudes.